Nuclear power in the twenty-first century (Part II) - The economic value of plutonium - Christian R. von Hirschhausen (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
Although plutonium has been studied by different disciplines (such as technology and innovation studies, political sciences) since its discovery, back in 1940 at the University of California (Berkeley), the resource and environmental economic literature is still relatively scarce; neither does the energy economic literature on nuclear power consider plutonium specifically, e.g. Davis (2012) or Lévêque (2014). However, interest in the topic is increasing, driven by a variety of factors: Thus, in the context of the low-carbon energy transformation and climate change mitigation, interest in non-light-water nuclear technology, including so-called 'Generation IV' fast neutron reactor concepts and SMR ('small modular reactors') non-light-water reactor concepts, supposedly to become competitive in some near time span, is rising, not only in Russia and China, but also in the US, Japan, Korea, and Europe (IAEA 2018; MIT 2018; Zhang 2020; Murakami 2021). This paper provides a review of resource and environmental economic issues related to plutonium, and presents insights from ongoing research. In particular, we ask whether after decades of unsuccessful attempts to use plutonium for electricity generation in the 20th cenutry, resource and energy economic conditions have changed sufficiently to reverse this result in the 21st century. In the analytical framework, we explore determinants of the value of plutonium, by comparing it with the economics of the dominant nuclear energy, the light-water reactor (LWR) using a once-through fuel process. Three questions emerge and are addressed subsequently: i) Can plutonium benefit from shortages of uranium and binding constraints on uranium supply for light-water nuclear power plants?; ii) can future nuclear reactors developments become competitive through standardized mass production of SMRs ('small modular reactors'); and iii) can plutonium be efficiently abated? We find that the answer to the three questions is negative, and conclude that there are no indications of more favorable economic conditions for the commercial deployment of plutonium today than there were in the last century.
Keywords: O33; Q53; Q47; L97; 330; nuclear power; uranium; plutonium; resources; economics; technology; innovation